Delayed Distant Recurrence of a Uveal Melanoma 4 Decades after Enucleation - Nils A. Eide; Agate Noer; Henrik Jespersen; Peter Jebsen; Jürgen Geisler (Case Reports in Oncology)
Introduction: This report presents a case of an exceptionally delayed distant recurrence of a choroidal melanoma, occurring 4 decades after the enucleation of the affected eye. Case Presentation: In 1977, a 29-year-old man underwent enucleation for a choroidal melanoma. At the age of 68 years, he was diagnosed with advanced prostate cancer. Although the metastatic prostate cancer responded to treatment, a persistent lung lesion warranted further examination. A lung biopsy, somewhat surprisingly, confirmed the presence of melanoma metastasis, 4 decades after the enucleation. The cells were positive for Melan-A, while no BRAF mutation was identified. Two years later, new lesions appeared in the liver, and CT showed progression with multiple new sites. A liver biopsy revealed again melanoma recurrence, and its choroidal origin was verified by the presence of a GNA11 mutation. The patient underwent radiation therapy for the lung and liver lesions, followed by immunotherapy. However, the patient died 11 months after the recurrence in the liver. In this case report, the micrometastatic melanoma cells appear to have remained dormant for an extended period, before the patient’s treatment in 1977, but the reason for the late reactivation from the dormant state remains unclear. Conclusion: The recurrence of a choroidal melanoma is substantiated by the histopathological and molecular analyses, including the finding of a GNA11 mutation. This case exemplifies a remarkably delayed distant recurrence of a choroidal melanoma, which manifested clinically 40 years following enucleation.